2016
DOI: 10.1038/srep18618
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific hybridization, polyploidization and backcross of Brassica oleracea var. alboglabra with B. rapa var. purpurea morphologically recapitulate the evolution of Brassica vegetables

Abstract: Brassica oleracea and B. rapa are two important vegetable crops. Both are composed of dozens of subspecies encompassing hundreds of varieties and cultivars. Synthetic B. napus with these two plants has been used extensively as a research model for the investigation of allopolyploid evolution. However, the mechanism underlying the explosive evolution of hundreds of varieties of B. oleracea and B. rapa within a short period is poorly understood. In the present study, interspecific hybridization between B. olerac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…These results indicate that ploidy level can affect both leaf morphological and anatomic structures as well as physiological function. Our results are congruent with studies of newly re-synthesized allotetraploid B. napus, which demonstrate 70% of life history traits differ from the parental diploids [51], and which indicate that aspects of leaf morphology can exhibit transgressive phenotypes [52, 53]. …”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that ploidy level can affect both leaf morphological and anatomic structures as well as physiological function. Our results are congruent with studies of newly re-synthesized allotetraploid B. napus, which demonstrate 70% of life history traits differ from the parental diploids [51], and which indicate that aspects of leaf morphology can exhibit transgressive phenotypes [52, 53]. …”
Section: Discussionsupporting
confidence: 90%
“…As a prominent mode of speciation in flowering plants, allopolyploidy can cause genomic changes, including chromosomal rearrangements and changes in gene expression45464748. Recent studies have indicated the unequal expression of orthologous genes in allotetraploids such as Gossypium 1349, Brassica 47, Oryza minuta 50 and the synthetic allopolyploid Arabidopsis51, and the gene expression levels in these allopolyploids deviated from the expression of their orthologous genes in the progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the unequal expression of orthologous genes in allotetraploids such as Gossypium 1349, Brassica 47, Oryza minuta 50 and the synthetic allopolyploid Arabidopsis51, and the gene expression levels in these allopolyploids deviated from the expression of their orthologous genes in the progenitors. In our study, the expression patterns of genes in G. hirsutum revealed considerable differences from the expression of their orthologous genes in its progenitors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…'Yangyou6'. PCR analysis on S0 and S1 generation was performed using SSR primers in Table (Zhang et al, ). The young flower buds (~2 mm) of S0 generation were collected and fixed in Carnoy's solution (3:1 ethanol:acetic acid, v/v) for 24 hr, and then stored in 70% ethanol at 4℃.…”
Section: Methodsmentioning
confidence: 99%